Changes of augmentation index early after ischaemic stroke predict functional outcome. (2nd September 2020) - Kowalczyk, Kamil; Jabłoński, Bartosz; Kwarciany, Mariusz; Karaszewski, Bartosz; Narkiewicz, Krzysztof; Gąsecki, Dariusz
Abstract: Purpose: Outcome after ischaemic stroke (AIS) depends on multiple factors, including values of blood pressure (BP) and arterial stiffness (AS) in the early phase. It is also known that stroke outcome is affected by BP variability; however, the influence of AS oscillations in the early phase of stroke on its prognosis is unknown. The aim of our study was to assess the relationship between changes of AS markers and stroke outcome. Materials and methods: Baseline clinical data, BP parameters, and markers of AS (pulse wave velocity [PWV], augmentation index [AIx]) were assessed 1, 6, and >90 days after AIS. The outcomes were defined using modified Rankin scale (mRS) score: early favourable (EFO) and early poor (EPO), as mRS ≤1 and >2 points at discharge, respectively; late favourable (LFO) and late poor (LPO), as mRS ≤1 and >2 points on day >90, respectively. Results: In the recruited 50 patients (62.2 ± 12.1 years, 68% males), BP and PWV decreased while AIx did not change within 90 days after AIS. Twenty-eight patients (56%) had EFO, 10 (20%) – EPO, 29 (58%) – LFO, and 9 (18%) – LPO. In univariate analysis, rise in AIx in days 1–6 was associated with EFO (odds ratio [OR] = 1.09, 95% confidence interval [CI] = 1.02–1.17, p  = 0.01) and LFO (OR = 1.08; 95%CI = 1.01–1.14, p  = 0.02), whereas decrease in AIx in days 1–6 was associated with EPO (OR = 1.07, 95%CI = 1.00–1.15, p  = 0.05). For EFO and LFO, the relationships remained significant after including confounders ( p  = 0.03 and p  = 0.03, respectively). Conclusions: Rise in AIx within one week after ischaemic stroke may be of additional importance in determining better early and late favourable functional outcome.